Efficacy of Topical 0.05% Isotretinoin Gel Versus 0.1% Adapalene Gel in The Treatment of Mild to Moderate Acne Vulgaris - Saleem, Summaya; Raza, Naeem; Saleem, Nida; Ullah, Saleem; Yasmin, Ghazala; Yousaf, Farrah (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare the efficacy of topical 0.05% Isotretinoin gel versus 0.1% Adapalene gel in treating mild to moderate acne vulgaris. Study Design: Quasi-Experimental study. Place and Duration of Study: Department of Dermatology, Pak Emirates Military Hospital (PEMH), Rawalpindi Pakistan, From Feb to Jul 2018. Methodology: A total of ninety-two patients aged 12 to 25 years with mild to moderate facial acne vulgaris were enrolled and divided into two treatment Groups, Group-A (0.05% Isotretinoin Gel) and Group-B (0.1% Adapalene Gel). Efficacy was measured at 12 weeks post-treatment. Results: Treatment was found efficacious in 84.8% (n=39/46) of patients in Group-A and 50.0% (n=23/46) of patients in Group-B (p= 0.001). There were similar results when treatment efficacy in both Groups was disease severity. In all cases,efficacy was better in Group-A (p<0.05). Conclusions: The efficacy of topical 0.05% Isotretinoin gel was better than topical 0.1% Adapalene gel for treating mild to moderate acne vulgaris.